Good Corporate Governance, Profitabilitas, Ukuran Perusahaan dan Struktur Modal - Subing, Hesty Juni Tambuati (Universitas Multimedia Nusantara, 2017)
The purpose of this research is to know about the effect of these factors Corporate Governane proxy by Institutional Ownership and Number of Board of Directors, Firm Size, and Return On Asset in basic industry and chemistry towards capital structure, and also to determine which of those factors having powerful effect to the capital structure. This research is using secondary data, such as the financial reports, annual reports and other related information of basic industry and chemistry listed in Indonesian Stock Exchange which sample were taken from 45 companies for the period of 2013 to 2014, and the choosing of these samples was based on the purposive sampling method. Panel data is used to test the effect of Institutional Ownership, Board of Directors, Return on Asset and Firm Size among as independent variables, in regard to capital structure as dependent variables. The result shows that only Return On Asset have significant effect to the Capital Structure in the basic industry and chemistry. Meanwhile Institutional Ownership, Board of Directors and Firm Size have no effect to the Capital Structure in the basic industry and chemistry. Keywords: Institutional Ownership, Board of Directors, Return On Asset, Firm Size, Capital Structure